Teaching the Present Simple Tense and the third conditional to the students by using PPP method and writing skill. - Khabibulloeva Gulchekhra Komiljonovna; Norqulova Dilnoza Rustam qizi (Global Scientific Publishing, 2023)
There are several methods that can teach writing skill in English to the beginner learners as well-advanced students. One of the famous deductive and effective method of them is – PPP (presentation, practice and production). PPP- is a technique in teaching is simple way to introduce new topic or vocabulary to students. It will be useful for learning foreign languages in the classroom. It possesses three stages that helps students to learn, understand and practice new vocabulary
Keywords: understand; students; learning; vocabulary